An integrated intervention of computerized cognitive training and physical exercise in virtual reality for people with Alzheimer's disease: The jDome study protocol - Gambella, Elena; Margaritini, Arianna; Benadduci, Marco; Rossi, Lorena; D'Ascoli, Paola; Riccardi, Giovanni R.; Pasquini, Sara; Civerchia, Patrizia; Pelliccioni, Giuseppe; Bevilacqua, Roberta; Maranesi, Elvira (Frontiers in Neurology, 2022)
Introduction Alzheimer's disease is a neurodegenerative syndrome characterized by cognitive deficits, loss of daily functions, and mental and behavioral disorders, which cause stress and negatively affect the quality of life. Studies in the field suggest that combining cognitive training with physical activity can reduce the risk of developing the disease and, once neurodegeneration has begun, it slows its progress. In particular, virtual reality and augmented reality administer cognitive stimulation while providing a link to autobiographical memory through reminiscence, enabling the improvement of the person's quality of life. The present protocol aims to evaluate the effectiveness of cognitive and physical treatments, integrated with the addition of virtual reality and reminiscence elements, using the Brainer software, in which people will find cognitive training, and the jDome® BikeAround™ system, which will allow participants to pedal along a personalized path projected on a schematic, using an exercise bike connected to the system. Methods and analysis For this study, 78 patients with mild Alzheimer's dementia were recruited and divided into the Experimental Group (EG) and Control Group (CG). Sixteen treatment sessions of 60 min each were conducted for both groups (2 training sessions per week, for 8 weeks), including 1 patient at a time. The EG received cognitive treatment with Brainer and physical training with jDome, while the CG received cognitive treatment with Brainer and physical training with a classic bicycle. The evaluation mainly focused on the assessment of the person's cognitive status. Other analyses were conducted on the quality of life, mood, behavioral disorders, and physical function, which were considered secondary outcomes. Discussions The ultimate goal of the present study is to test the effectiveness of a treatment for people with mild Alzheimer's focused on the integration of cognitive training and aerobic physical activity, using an exercise bike, with the addition of virtual reality and reminiscence elements. Ethics and dissemination The study was approved by the Ethics Committee of the IRCCS INRCA. It was recorded in ClinicalTrials.gov on 2 June 2022 with the number NCT05402423. The study findings will be used for publication in peer-reviewed scientific journals and presentations in scientific meetings.